Poetics and narrative function of Tobit 6 - Brum Teixeira, José Lucas (Deuterocanonical and cognate literature studies, 2019)
Frontmatter -- Preface / Mazzinghi, Luca -- Acknowledgements -- Contents -- Abbreviations -- Introduction -- Greek Text for Tob 6 -- 1. Some General Issues Regarding Tobit -- 2. Literary and Narrative Remarks on Tob 6 -- 3. Exegesis of Tobit 6 -- 4. Poetics and Narrative Function of Tobit 6: Synthesis and Conclusions -- Bibliography -- Index -- Subject Index